2018
DOI: 10.5194/acp-2018-744
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intercomparison of mid-latitude tropospheric and lower stratospheric water vapor measurements and comparison to ECMWF humidity data

Abstract: Abstract. Accurate measurement of water vapor in the climate sensitive region near the tropopause turned out to be very challenging. Unexplained systematic discrepancies between measurements at low water vapor mixing ratios made by different instruments on airborne platforms have limited our ability to adequately address a number relevant scientific questions on the humidity distribution, cloud formation and climate impact in that region. Therefore, during the past decade, the scientific community has undertak… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…Restraining our comparison to the same altitude and volume mixing ratio ranges, the Pearson's r coefficient is of 0.975 and the associated r 2 coefficient is of 0.998, similar to those reported in Singer et al, (2022) and Kaufmann et al, (2016). In Kaufmann et al, (2018), the reported r 2 values y from 0.948 to 0.996, depending on the instrument pair considered and environmental conditions, in the 1 to 1000 ppmv range. In the range 0-7.5 km, RH values measured by iMet-4 sondes compare really well with RH values calculated from FPH and Pico-Light measurements if the T (predominantly) and P measurements used for the calculation of RH come from the IMet sonde onboard.…”
Section: Descriptions Of the Compared Datasetssupporting
confidence: 76%
See 2 more Smart Citations
“…Restraining our comparison to the same altitude and volume mixing ratio ranges, the Pearson's r coefficient is of 0.975 and the associated r 2 coefficient is of 0.998, similar to those reported in Singer et al, (2022) and Kaufmann et al, (2016). In Kaufmann et al, (2018), the reported r 2 values y from 0.948 to 0.996, depending on the instrument pair considered and environmental conditions, in the 1 to 1000 ppmv range. In the range 0-7.5 km, RH values measured by iMet-4 sondes compare really well with RH values calculated from FPH and Pico-Light measurements if the T (predominantly) and P measurements used for the calculation of RH come from the IMet sonde onboard.…”
Section: Descriptions Of the Compared Datasetssupporting
confidence: 76%
“…Considering all 6 flights, Singer et al, (2022), reported average relative difference varying from -0.4 to 1.9%. Kaufmann et al, (2018) reported intercomparisons in the UTLS between in situ aircraft hygrometers during the ML-CIRRUS campaign: FISH, HAI (Buchholz et al, 2017), SHARC and AIMS (Kaufmann et al, 2016;Thornberry et al, 2013). The relative difference between each instruments was calculated against a reference value which was calculated using the average of measurements from a combination of several of these instruments, varying upon atmospheric conditions.…”
Section: Descriptions Of the Compared Datasetsmentioning
confidence: 99%
See 1 more Smart Citation